The Argentine Naval Prefecture and the «Paradigm Shift» in the Pursuit of Illegal Fishing. A look from the Green and Blue Criminologies (Delito y Sociedad, 2023)
The article takes a green and blue criminology stance to analyze the problem of illegal fishing in Argentina. Based on the study of regulatory instruments and interviews, the study addresses the role of the Prefectura Naval Argentina (PNA) within the exclusive economic zone (ZEE) and beyond mile 200 in the face of harmful fishing actions by foreign vessels. On the one hand, the article focuses on the use of criminal law as an instrument to control illegal fishing, highlighting the problems and limitations of this approach. On the other hand, the study focuses on the work of the PNA in the search for non-punitive solutions. It mainly analyzes the intervention of this security agency in the Huali 8 case, identified by the PNA as a "paradigm shift" in the control of illegal fishing within the ZEE, and the intersectoral and interdisciplinary work as a non-punitive response to unregulated fishing in the maritime space beyond mile 200. As a whole, from the critical paradigm of green and blue criminologies, this article seeks to focus on the global South and on how one of the agencies destined to exercise punitive power sought to explore alternative courses of action, prioritizing the care of the aquatic environment without the need for more punishment.
Keywords: Green criminology; blue criminology; southern criminology; illegal fishing; non-punitive solutions; Argentine Naval Prefecture